The Electrostatic Generator of Mende (Global Journal of Science Frontier Research, 2020)
The survey of the methods of separation and accumulation of charges is carried out and the existing constructions of electrostatic generators are examined. Is proposed the new method of the separation of electric charges in the liquids, which flow in the magnetic field. Is given the schematic of the electrostatic generator, based on the application of a method of the magnetic separation of charges, and they are represented the results of experimental studies.